"Now I Am Myself": Exploring How People With Poststroke Aphasia Experienced Solution-Focused Brief Therapy Within the SOFIA Trial. (September 2021) - Northcott, Sarah; Simpson, Alan; Thomas, Shirley; Barnard, Rachel; Burns, Kidge; Hirani, Shashivadan P.; Hilari, Katerina
Aphasia, a language disability, can profoundly affect a person's mood and identity. The experiences of participants who received Solution-Focused Brief Therapy, a psychological intervention, were explored in the Solution-Focused brief therapy In poststroke Aphasia (SOFIA) Trial. Thirty participants with chronic aphasia, 14 with severe aphasia, participated in in-depth interviews that were analyzed using framework analysis. Two overarching themes emerged: valued therapy components (exploring hopes, noticing achievements, companionship, sharing feelings, and relationship with therapist) and perceptions of progress (mood, identity, communication, relationships, and independence). Participants were categorized into four groups: (a) "changed, " where therapy had a meaningful impact on a person's life; (b) "connected, " where therapy was valued primarily for companionship; (c) "complemental, " where therapy complemented a participant's upward trajectory; and (d) "discordant, " where therapy misaligned with participants' preference for impairment-based language work. This study suggests that it is feasible to adapt a psychological therapy for people with aphasia, who perceive it as valuable.